Distribution of Flood Risk Area in Bodri Watershed of Kendal Regency - Husna Fauzia; Eka Cahyaningsih; Hery Nugroho Hariyanto; Satya Budi Nugraha (Program Pascasarjana Universitas Sriwijaya, 2021)
Flooding is a catastrophic phenomenon that can occur due to various factors, such as uncontrolled land-use changes, climate change, and weather anomalies, and drainage infrastructure damage. The Bodri watershed in Kendal Regency is one of the watersheds in Central Java, which is categorized as critical based on Decree No. 328/Menhut-II/2009. Some of the problems in the Bodri watershed include land use that is not suitable for its designation, flooding, erosion, and landslides. This study aims to conduct spatial modeling to create flood hazard maps and flood risk level maps in the Bodri watershed. The method used is hydrograph analysis, flood modeling, analysis of potential flood hazards, and analysis of flood risk levels. Analysis of the potential for flood hazards from the spatial modeling inundation map with the input of the flood peak return period of 2 years (Q2), 5 years (Q5), and 50 years (Q50). Vulnerability analysis based on land use maps of flood hazard areas. The distribution of flood-prone areas in the Bodri watershed is in Pidodo Kulon Village, Pidodo Wetan Village, and Bangunsari Village.